Complex Aspects of the Organization Educational Process in the Context of the Pandemic Coronavirus (Covid-19) - Abbasov Bahadir Asatillaevich (Genius Publishing Group, 2022)
In the context of the coronavirus (COVID-19) pandemic, which has not yet reduced its influence in the educational process in universities, very difficult times have come, which required finding a way out of this situation with the least losses. We can confidently say that the academic discipline "Physical Culture and Sports" is one of the few academic disciplines that have affected the negative effects of quarantine to the greatest extent. This article tells about the level of satisfaction of students in such challenging quarantine conditions.
Keywords: Physical culture; sports; theory of sports; theoretical training